2010
DOI: 10.3382/ps.2010-00787
|View full text |Cite
|
Sign up to set email alerts
|

Effect of eggshell temperature and oxygen concentration on survival rate and nutrient utilization in chicken embryos

Abstract: Environmental conditions during incubation such as temperature and O(2) concentration affect embryo development that may be associated with modifications in nutrient partitioning. Additionally, prenatal conditions can affect postnatal nutrient utilization. Using broiler chicken embryos, we studied the effects of eggshell temperature (EST; 37.8 or 38.9 degrees C) and O(2) (17, 21, or 25%) applied from d 7 until 19 of incubation in a 2 x 3 factorial design. Effects of these factors on embryonic survival, develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
33
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 40 publications
6
33
1
3
Order By: Relevance
“…Molenaar et al (2010b) indicated that a constant EST throughout the incubation period can only be achieved by the SS setters because the parameters can be adjusted to compensate for excess embryo heat production. Therefore, if we consider that the main difference between the systems is incubation temperature control, these results agree with those obtained by Lourens et al (2005) and Molenaar et al (2010a), who found a lower CL in birds subjected to higher EST (38.9 °C) compared with those incubated under normal EST (37.8 °C).…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Molenaar et al (2010b) indicated that a constant EST throughout the incubation period can only be achieved by the SS setters because the parameters can be adjusted to compensate for excess embryo heat production. Therefore, if we consider that the main difference between the systems is incubation temperature control, these results agree with those obtained by Lourens et al (2005) and Molenaar et al (2010a), who found a lower CL in birds subjected to higher EST (38.9 °C) compared with those incubated under normal EST (37.8 °C).…”
Section: Resultssupporting
confidence: 81%
“…By contrast, various experiments indicated that chicks hatched in incubation systems managed with high EST exhibited lower yolk-free body mass at hatching (Leksrisompong et al, 2007;Lourens et al, 2007;Molenaar et al, 2010a;Molenaar et al, 2011;Shim and Pesti, 2011). The differences between these results may be due to other factors in addition to temperature, such as the interaction with batches of eggs with different ages that were incubated inside the machine.…”
Section: Resultscontrasting
confidence: 40%
“…Most of the unhatched chicks in very high EST were observed to be malpositioned, mainly with their head over their wing. Increased malpositions at high EST were previously found by Molenaar et al (2010), who described increased numbers of head between legs and head over wing embryos when they were incubated at an EST of 38.9°C from E7 onward compared with normal EST (37.8°C throughout).…”
Section: Discussionmentioning
confidence: 73%
“…From E19.5 onward, hatched chicks (n = 133) were pulled every 12 h. Chicks were weighed, their length was recorded from the tip of the beak to the tip of the middle toe, excluding the nail (Molenaar et al, 2010), and navel condition was scored as 1 (a clean and closed navel), 2 (a black button or gap of <2 mm), or 3 (a black button or gap of >2 mm; Molenaar et al, 2010). Residual yolk was removed and weighed after cervical dislocation.…”
Section: Measurementsmentioning
confidence: 99%
See 1 more Smart Citation